Assessment of project activity and development perspectives - Muradov, I.; Səfəralıyeva, I. (Assessment of project activity and development perspectives, 2026)
Project activity is a crucial component in organizational growth and innovation. Evaluating project performance enables managers to identify strengths, weaknesses, and future development opportunities (Mammadov, 2020). This study examines current methods of project assessment and proposes strategies for improving project efficiency and sustainability. The research emphasizes the integration of modern project management tools, training programs, and sustainability considerations as essential for achieving long-term project success (Brown & Green, 2022).
Keywords: project activity; development perspectives; project management; organizations; potential risks; project assessment; strategic management